2020
DOI: 10.1007/s13167-020-00217-y
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids against the Warburg phenotype—concepts of predictive, preventive and personalised medicine to cut the Gordian knot of cancer cell metabolism

Abstract: The Warburg effect is characterised by increased glucose uptake and lactate secretion in cancer cells resulting from metabolic transformation in tumour tissue. The corresponding molecular pathways switch from oxidative phosphorylation to aerobic glycolysis, due to changes in glucose degradation mechanisms known as the 'Warburg reprogramming' of cancer cells. Key glycolytic enzymes, glucose transporters and transcription factors involved in the Warburg transformation are frequently dysregulated during carcinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 223 publications
0
85
0
Order By: Relevance
“…The observation revealed that cancer cells receive enormous amounts of glucose compared to surrounding non-malignant tissue. The repression of cancer cell respiration and the enhancement of glucose fermentation into lactate were also identified [ 11 , 63 ]. Recent evidence has revealed the specific molecular mechanisms responsible for switching from OXPHOS to aerobic glycolysis.…”
Section: Hypoxic Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The observation revealed that cancer cells receive enormous amounts of glucose compared to surrounding non-malignant tissue. The repression of cancer cell respiration and the enhancement of glucose fermentation into lactate were also identified [ 11 , 63 ]. Recent evidence has revealed the specific molecular mechanisms responsible for switching from OXPHOS to aerobic glycolysis.…”
Section: Hypoxic Conditionsmentioning
confidence: 99%
“…Recent evidence has revealed the specific molecular mechanisms responsible for switching from OXPHOS to aerobic glycolysis. Alterations in molecular pathways, including PI3K/Akt/mTOR, specific genes such as cMYC and p53 , and changes in epigenetic machinery directly participate in the regulation of cancer metabolism [ 11 , 64 , 65 , 66 , 67 ]. HIF-1 plays an essential role in the regulation of changes leading to the Warburg phenotype; it acts as a central regulator of glucose metabolism and cell proliferation.…”
Section: Hypoxic Conditionsmentioning
confidence: 99%
See 3 more Smart Citations